Final product conservation dynamic evaluation of a food obtained by the potato solid state fermentation - Borras-Sandoval, Luis Miguel; Iglesias, Arabel Elías; Saavedra-Montañez, Gabriel Fernando (Universidad Pedagógica y Tecnológica de Colombia, 2015)
The present work shows the solid state fermentation effect on a type of food prepared on potato tuber (Solanum tuberosum) basis and their possible use in animal feed. Some chopped fresh potato was mixed with a drying fibrous material (alfalfa meal), molasses, urea, a microbial preparation, mineral premix, calcium carbonate and sodium sulfate and then fermented according to the time and temperature previously established (48 h and 20 °C), in plastic bags of 50 kg capacity. The Fes-potato product was sampled the day one and then at thirty to ninety days respectively. The Fes-potato product showed significant changes in the fermentation indicators evaluated. The pH fell steadily from baseline (6.3) to complete the evaluation (pH 4.86) at 48 hours, regardless of the incubation temperature. Something similar happened with the dry matter (MSI) and the fibrous component (FDN-FDA), which decreased with the fermentation time, sensible improving the product digestion. The Fes-potato is a simple process to take advantage of the biotechnology tubers crop residues, and to generate an energy—protein food, consistent with the content in MS fermentative indicators that could be used in animal feed; plus it should help to counteract environmental pollution.